2007
DOI: 10.1002/cncr.23070
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of survival from urachal cancer

Abstract: Objective Antineutrophil cytoplasmic antibody–associated vasculitis (AAV) is characterized by necrotizing vessel wall inflammation, paralleled by the detachment of endothelial cells. The repair of such endothelial defects is crucial for the maintenance of regular structure and function of the injured vessels. Bone marrow–derived endothelial progenitor cells (EPCs) are thought to play a pivotal role in the regeneration of damaged endothelium. The aim of this study was to investigate whether EPCs are involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
176
1
26

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(213 citation statements)
references
References 18 publications
10
176
1
26
Order By: Relevance
“…All recurrences were at distant metastatic sites, with the lung being the most common. This result was in agreement with previous studies [27]. …”
Section: Discussionsupporting
confidence: 94%
“…All recurrences were at distant metastatic sites, with the lung being the most common. This result was in agreement with previous studies [27]. …”
Section: Discussionsupporting
confidence: 94%
“…Molina et al conducted a retrospective study on urachal carcinoma including 49 patients and found that 89% were adenocarcinomas, whereas sarcomas and transitional cell carcinomas represented ~4%. Of the adenocarcinomas, 63.6% may produce mucin (10). The result is similar to those of Paner et al (11).…”
Section: Discussionsupporting
confidence: 88%
“…The prognosis of patients with urachal cancer is generally considered poor because it is generally diagnosed at an advanced disease stage and is associated with a high frequency of recurrence after primary treatment. The 5-year overall survival (OS) is reported to be 34-40% [2,3]. In particular, the median survival time for stage IV patients (metastatic disease) is 1.3 years compared with a median survival of 10.8 years for stage I/II patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…The 5-year overall survival (OS) is reported to be 34-40% [2,3]. In particular, the median survival time for stage IV patients (metastatic disease) is 1.3 years compared with a median survival of 10.8 years for stage I/II patients [3]. …”
Section: Introductionmentioning
confidence: 99%